Factors And Interests That Unite Citizens - Jamila, Matkarimova; Rozigul, Umarova; Nassiba, Yunusova (International Journal of Membrane Science and Technology, 2023)
This article examines the efforts of citizen associations to further develop democracy and strengthen civil society. It has been analyzed by scientific studies that associations that unite citizens can be generators of social trust or vice versa.